Predicting the Next Eye Pathogen: Analysis of a Novel Adenovirus - Christopher M. Robinson (American Society for Microbiology, 2013)
ABSTRACT For DNA viruses, genetic recombination, addition, and deletion represent important evolutionary mechanisms. Since these genetic alterations can lead to new, possibly severe pathogens, we applied a systems biology approach to study the pathogenicity of a novel human adenovirus with a naturally occurring deletion of the canonical penton base Arg-Gly-Asp (RGD) loop, thought to be critical to cellular entry by adenoviruses. Bioinformatic analysis revealed a new highly recombinant species D human adenovirus (HAdV-D60). A synthesis of in silico and laboratory approaches revealed a potential ocular tropism for the new virus. In vivo, inflammation induced by the virus was dramatically greater than that by adenovirus type 37, a major eye pathogen, possibly due to a novel alternate ligand, Tyr-Gly-Asp (YGD), on the penton base protein. The combination of bioinformatics and laboratory simulation may have important applications in the prediction of tissue tropism for newly discovered and emerging viruses. IMPORTANCE The ongoing dance between a virus and its host distinctly shapes how the virus evolves. While human adenoviruses typically cause mild infections, recent reports have described newly characterized adenoviruses that cause severe, sometimes fatal human infections. Here, we report a systems biology approach to show how evolution has affected the disease potential of a recently identified novel human adenovirus. A comprehensive understanding of viral evolution and pathogenicity is essential to our capacity to foretell the potential impact on human disease for new and emerging viruses.